Roman Anglesey: Recent Discoveries. (5th November 2018) - Hopewell, David
ABSTRACT: A series of projects by Gwynedd Archaeological Trust has identified two significant sites on the island of Anglesey. The first is a trading settlement on the shore of the Menai Strait which provides evidence for a hitherto unknown level of Romanisation in the remote west of the province. The second is a late first- to early second-century fortlet on the northern coast of the island that probably functioned as both a navigational aid and a point of strength at a landing place. The presence of a fourth-century watchtower on Carmel Head was also confirmed by excavation and its role in the late Roman coastal defence system is considered.